More electric aircraft starter-generator system with utilization of hybrid modulated model predictive control - Yoeh, Seang Shen; Yang, Tao; Tarisciotti, Luca; Hill, Christopher Ian; Bozhko, Serhiy (2016)
The current trend for future aircraft is the adoption of the More Electric Aircraft (MEA) concept. The electrical based starter-generator (S/G) system is one of the core ideas from the MEA concept. The PI based control scheme has been investigated in various papers for the permanent magnet based S/G system. Different control schemes are to be considered to improve the control performance of the S/G system. A type of non-linear control called Model Predictive Control (MPC) is considered for its capability to accomplish fast dynamic control performance. The Modulated Model Predictive Control (variant of MPC with an intrinsic modulator) was presented that showed considerably better control performance than the standard MPC. A control scheme is presented in this paper that utilises PI controllers for the outer loop and Modulated Model Predictive Control for the inner loop that covers operation for both starter and generator modes. Simulation analyses are carried out to compare between the proposed control and a full cascaded PI control scheme. The proposed control is also subjected to parameter variation tests for performance evaluation.